Mutual image impacts of events and host destinations: What we know from prior research - Christian Dragin-Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2016)
In the highly competitive marketplace for tourists and talented citizens, events have become increasingly important in acting as image builders for their host destinations. Equivalently, the image of a destination can have an impact on event perceptions, resulting in careful considerations for event managers and destination stakeholders to make when pairing an event with a host destination. This has resulted in a significant increase in publishing activity of image impacts on events and host destinations in the past decade, eventuating in a wide array of theories, methods and results. As a contribution to event and destination image impact research, this paper systematically conducts a review process and identifies 37 peer-reviewed articles that fall within its established research criteria, thereby synthesizing and gaining new perspectives, as well as presenting new implications by conjoining aspects of destination and event image research not previously compared.
Keywords: 330; Events; Image Impact; Event Tourism; Destination Image; Literature Review